1997
DOI: 10.1093/humrep/12.2.286
|View full text |Cite
|
Sign up to set email alerts
|

Fertilization with human testicular spermatids: four successful pregnancies

Abstract: Between July 1995 and May 1996, 36 patients with non-obstructive azoospermia of secretory origin underwent intracytoplasmic injection of spermatids. A previous histological biopsy was performed on all patients: 15 had spermatogenic arrest, a further 13 had Sertoli cell-only syndrome, and the remaining eight had post-cryptorchidism tubal atrophy. The ejaculate was duly examined and a complete absence of spermatozoa and spermatids was confirmed, with only bacteria and debris being found. Testicular sperm extract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0
1

Year Published

1998
1998
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(45 citation statements)
references
References 25 publications
0
44
0
1
Order By: Relevance
“…Tesarik et al [12,16] reported 7 cycles of ROSI (Sa type) with 46% fertilization rate with 10% of syngamic zygotes. Antinori et al [17] reported a 56% rate of fertilization, while Vanderzwalmen et al [18] reported 12% fertilization. Since successful pregnancies have been reported after round spermatid injection, we are encouraged to attempt the use of testicular round spermatid (Sa) obtained in a biopsy sample of a nonobstructive azoospermia.…”
Section: Discussionmentioning
confidence: 99%
“…Tesarik et al [12,16] reported 7 cycles of ROSI (Sa type) with 46% fertilization rate with 10% of syngamic zygotes. Antinori et al [17] reported a 56% rate of fertilization, while Vanderzwalmen et al [18] reported 12% fertilization. Since successful pregnancies have been reported after round spermatid injection, we are encouraged to attempt the use of testicular round spermatid (Sa) obtained in a biopsy sample of a nonobstructive azoospermia.…”
Section: Discussionmentioning
confidence: 99%
“…Several normal clinical pregnancies following round spermatid injection have been reported (Antinori et al 1997, Kahraman et al 1998, Barak et al 1998, although disappointingly poor fertilization and subsequent embryonic development are common outcomes (Levran et al 2000, Vicdan et al 2001. Fertilization of cynomolgus macaque oocytes with round spermatids has been reported; however, the only pregnancy established aborted at day 103 (Ogonuki et al 2003).…”
Section: Cytoskeletal Architecture During Primate Icsimentioning
confidence: 99%
“…Round or elongated spermatids were collected from patients with non-obstructive azoospermia who did not have mature spermatozoa in their testes, and some of their partners became pregnant and delivered babies. Table 1 summarizes the major reports on round spermatid injection [39][40][41][42][43][44][45][46][47][48]. As can be seen in the table, the rates of fertilization and delivery had been low, but the cause of these poor results had not yet been clearly identified.…”
Section: Spermatid Injectionmentioning
confidence: 99%
“…Artificial oocyte activation is therefore probably necessary when round spermatids are used in microinjection. Excessive ooplasm aspiration [39,40,42,43,45], calcium ionophore treatment [41,45], and electric stimulation [59] for artificial oocyte activation have been introduced when round human spermatids are used. But with these artificial oocyte activation methods, Ca 2+ oscillation is not induced.…”
Section: Oocyte Activating Factormentioning
confidence: 99%